Efficiency application of Brief Systemic Family Therapy in children and adolescents in Nayarit (Mexico) - Ávila Arellano, Issa María (2024)
This paper expose the design, development and evaluation of the Brief Systemic Therapy technique (Villarreal and Paz, 2015) applied to 40 patients (15 girls, 19 childs, 4 teenage women and 2 teenage men) in the state of Nayarit, Mexico during June 2019 to April 2022. A semi-structured interview was applied to the mother and/or father of each patient, were constructed analysis categories and review information about clinical records. We use the “Subjective Change” method (Castro, Krause y Frisancho, 2015), which is a whole of personal cognitions to support and optimizing personal assessment, generate behaviors andactions to improve life quality. The application of Brief Systemic Therapy support well-being of patients in affective, cognitive and behavioral areas.